Abiji Baby - Muhamad Shah, Muhamad Izwan; Mohd Fuad, Muhammad Izzat; Mohd Aris, Nur Zurulain; Abdul Razak, Noor Amira; Samsuddin, Khairul Barai'ah (2015)
ABIJI BABY is about business that supply the equipment for baby that has been gave innovation. The business located at Lot 18, KOTA FESYEN, JALAN LINGKARAN MITC, 75450 MELAKA, MALAYSIA. We choose this location because this is commercial areas that can attract people to promote our product. This business is about business partner that shares capital among the partners. Each member has contributed RM 20,000 and RM15,OOO and loan from CIMB Bank RM 85,000 and Affin Bank RM 85,000 as a capital to run this business. This business is about furniture that has been give an innovation by us. This business is wanted to promote the furniture at the market. The products that we want to introduce are Innovative Furniture that has easy function which are, the cot can be transform into small size and easy to handle. Moreover it can be successfully compete with our competitors in a few years ahead. This is because we saw the opportunity that this business has the potential to success in the future if we managed it very efficiently. It is because product that we offer is not well-known in Peninsular Malaysia and Borneo market and will give opportunity to them.